Forger's Progress : The Life of Francis Greenway - McGregor, Alasdair (EBL-Schweitzer, 2014)
Alasdair McGregor is the author of Frank Hurley: A Photographer's Life; Mawson's Huts: An Antarctic Expedition Journal; and Grand Obsessions: The Life and Work of Walter Burley Griffin and Marion Mahony Griffin, winner of the 2011 National Biography Award; and the coauthor of Australia's Wild Islands and The Kimberley: Horizons of Stone, both with Quentin Chester.